2017
DOI: 10.1371/journal.pone.0182049
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the reticulated python (Malayopython reticulatus ssp.): Conservation implications for the worlds’ most traded snake species

Abstract: As an important economic natural resource in Southeast Asia, reticulated pythons (Malayopython reticulatus ssp.) are primarily harvested from the wild for their skins—which are prized in the luxury leather goods industry. Trade dynamics of this CITES Appendix II listed species are complex and management approaches on the country or regional level appear obscure. Little is known about the actual geographic point-of-harvest of snakes, how genetic diversity is partitioned across the species range, how current har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Thus, there will be a significant economic impact on snake trading, which will result in substantial losses, if an outbreak of ferlavirus infection occurs. Although ferlavirus infection in snakes is of grave concern in Europe and the Americas 20 , information regarding ferlavirus infection in snakes from Thailand, where over 100 snake breeding farms are located, is lacking 18 , 21 23 . Epidemiology and disease surveillance of ferlavirus infection in all captive, farmed, and pet-owned snakes in Thailand are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there will be a significant economic impact on snake trading, which will result in substantial losses, if an outbreak of ferlavirus infection occurs. Although ferlavirus infection in snakes is of grave concern in Europe and the Americas 20 , information regarding ferlavirus infection in snakes from Thailand, where over 100 snake breeding farms are located, is lacking 18 , 21 23 . Epidemiology and disease surveillance of ferlavirus infection in all captive, farmed, and pet-owned snakes in Thailand are needed.…”
Section: Introductionmentioning
confidence: 99%
“…were detected in A. varanense infesting the lizard V. salvator [181]. Additionally, in Indonesia manual skin collection occurs in exotic animals such as wild snakes [182], lizards, and the Asiatic softshell turtle, Amyda cartilaginea. These practices highlight the importance of exercising caution and adopting appropriate measures to ensure the safety and well-being of all persons exposed to exotic species in new environments.…”
Section: Indonesiamentioning
confidence: 99%
“…Populations of Reticulated Pythons across the species' range are under immense pressure largely attributable to harvesting skins for the leather industry -it is the most widely traded snake species in the world -and retaliatory killing (Lang 2010;Murray-Dickson et al 2017). Although harvest- Vijayakumar and David (2006) indicated that habitat destruction and persecution played major roles in pre-tsunami population declines of pythons in the archipelago -and these continue today.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%
“…The recent thrust for economic development by promoting tourism and other activities (Giles 2018) on top of the ongoing clearing of forests for coconut plantations and human settlements and the unsustainable harvesting of natural resources associated with a growing human population (Saini 2013) might render the long-term survival of Reticulated Pythons in the Nicobar Archipelago untenable. Further complicating matters is that no specimens from the Nicobar Archipelago were included in the phylogenetic study by Murray-Dickson et al (2017), who emphasized that any conservation efforts must focus on genetically distinct populations. The survival of Reticulated Pythons in the archipelago will depend on detailed long-term studies focusing on the species' ecology and population status.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%